PHYSICAL CHARACTERISTICS OF MULTIFLORAL HONEY OF APIS DORSATA F. AND APIS CERANA INDICA FROM WESTERN GHATS OF KARNATAKA - M. V. BALASUBRAMANYAM (The Bioscan, 2011)
Multifloral honey of indigenous honeybee species, giant honeybee Apis dorsata and Indian hivebee Apis cerana indica from four districts of Western Ghats of Karnataka were determined during June 2010 to May 2011. Physical characteristics of moisture, viscosity, surface tension, optical density and refractive index were identified. Honey of A. dorsata display more moisture (23.55%), viscosity (78.41poise) and surface tension (108.56 dynes/cms) from Hassan and least of moisture (21.45%), viscosity (70.38poise) and surface tension (98.75 dynes/cms) from A. cerana in Madikeri. Optical density (0.54) was least for A. cerana honey from Chickamagalur and highest of 0.67 in A. dorsata honey from Dakshina Kannada. Refractive index (1.4832) was greatest for A. cerana honey from Madikeri and 1.4701 for A. dorsata honey from Hassan. The study confirms correlation among moisture, viscosity and surface tension of honey from honeybee species from geographical regions of Western Ghats. Variations occur in optical density of honey within honeybee species from different areas of Western Ghats. Refractive index of honey within honeybee species is inversely proportional to moisture. Apart from optical density and refractive index of honey all parameters tested were statistically significant at p<0.01. Results of the study confirmed the quality of honey of A. cerana and A. dorsata were equally good in the physical compositions which are discussed in ensuing paper.